First, multiply each term with each parenthesis by the term outside the parenthesis:
#0 = color(red)(4)(n - 4) - color(blue)(6)(n - 4)#
#0 = (color(red)(4) xx n) - (color(red)(4) xx 4) - (color(blue)(6) xx n) - (color(blue)(6) xx -4)#
#0 = 4n - 16 - 6n - (-24)#
#0 = 4n - 16 - 6n + 24#
Next, on the right side of the equation, group and combine like terms:
#0 = 4n - 6n - 16 + 24#
#0 = (4 - 6)n + 8#
#0 = -2n + 8#
Then, subtract #color(red)(8)# from each side of the equation to isolate the #n# term while keeping the equation balanced:
#0 - color(red)(8) = -2n + 8 - color(red)(8)#
#-8 = -2n + 0#
#-8 = -2n#
Now, divide each side of the equation by #color(red)(-2)# to solve for #n# while keeping the equation balanced:
#(-8)/color(red)(-2) = (-2n)/color(red)(-2)#
#4 = (color(red)(cancel(color(black)(-2)))n)/cancel(color(red)(-2))#
#4 = n#
#n = 4#